Psychological Problems of Elites and Masses in Heritage of D. Dontzov and V. Lypynskyj - Mojsijenko, Yaroslav (Psychological Prospects Journal, 2017)
The article analyzes the main works of ideologues of the Ukrainian national thought of the first half of the twentieth century – D. Dontsov and V. Lypynsky. The problem of the identification of socio-psychological ideas in the journalistic heritage has been updated. In their heritge the concepts of the national aristocracy and the concept of  the struggle of the active minority against the passive majority (V. Lypinsky), concept of self-sufficient nationalism (D. Dontsov) are tangent to the problems of psychological elitism. The idea of spontaneous consciousness          (V. Lypinsky) is singled out and analyzed. The author's understanding of the relationship between the elites and the masses through the personification phenomenon is revealed. It is shown that political leadership is conceived through the concept of imperialism. Psychological signs of imperialism are the spontaneous wish of a political leader to expand his power, faith in the rule of law, need and truthfulness of their actions              (V. Lipinsky). The psychological components of the concept of nationalism by                D. Dontsov are distinguished, These are characterized by aggressiveness, irrationality, devaluation of rational components of consciousness and appreciation of emotional and affective components, the primacy of subordinate and subgroup interests before the individual interests of the person. It is shown that the construct of will is the basis for the nation's creative conception for  both authors. It is assumed that the unifying consciousness of national self-realization is in common for both researchers as the determining psychological construct in the interaction between the masses and the elites. The assumption is made that the concepts and ideas developed by Ukrainian researchers are connected at the problematic level with world social and psychological concepts in the field of psychology of the masses and elites. The similarity of V. Lipinsky's elitological conceptions with S. Freud's psychoanalytical positions in relation to the interaction between the leader and the masses is noted.